Divorce prediction using Naive Bayes / Alia Hannani Ahmad Bakri - Ahmad Bakri, Alia Hannani (2024)
The study focuses on developing a divorce prediction system using the Naive Bayes algorithm, a widely used classifier. The system achieved 98% accuracy in predicting divorce based on a comprehensive dataset. This approach can aid professionals in marriage counselling and family therapy to identify high-risk couples and implement preventive measures. Furthermore, it can focus on enhancing the system's accuracy and applicability by expanding the dataset and incorporating more features.